(untitled) (Bangladesh Journal of Agricultural Research, 2010)
Eight hybrid tomato lines bred for heat tolerance by the Olericulture Division, BARI were studied to observe their fruit setting ability and yield performance under the hot, humid conditions at the Olericulture Farm of Bangladesh Agricultural Research Institute, Joydebpur, Gazipur during summer 2005. Percent fruit set in the lines was found to be within the range of 30 to 45 except C-7 (3×7) in which this was 52.85. The tallest plants having larger number of branches and the lowest flower drop were also observed in C-7 (3×7). Pollen viability ranged from 27.63 to 61.52 percent among the hybrids. The highest weight of individual fruits (56.02 g) and firmness (1.41 kg) was observed in C-5 (2×5). The largest fruit in respect of length and diameter was produced by C-8 (5x5). No significant variation was found among the lines in respect of days to 50% flowering and percent TSS. Significant difference wa observed for fruit number per plant ranging from 27 to 51. All of the lines produced remarkably high yields and C-7 (3x7) gave the highest yield per plant (1.73 kg) as well as per hectare (41.5 tons). The highest gross return (1867500 Tk/ha) and the maximum net return (1486748 Tk/ha) having the highest BCR (3.90) were recorded in C-7 (3×7). Keywords: Heat tolerant; tomato hybrid; hot; humid. DOI: 10.3329/bjar.v35i3.6442 Bangladesh J. Agril. Res. 35(3) : 367-373